Neuroscientific Research on the Processing of Easy Language - Borghardt, Liv; Deilen, Silvana; Fuchs, Julia; Gros, Anne-Kathrin; Hansen-Schirra, Silvia; Nagels, Arne; Schiffl, Laura; Sommer, Johanna (Frontiers in Communication, 2021)
In an increasingly networked world, people who cannot participate in written communication are particularly at risk of social exclusion. Like other concepts of barrier-free communication, Easy Language (“Leichte Sprache”) attempts to enhance perceptibility and comprehensibility of texts for people with reading impairments by means of a rule-based reduction of complexity on the text side. The underlying assumption of simplified languages is that the reduction of linguistic complexity correspondingly reduces cognitive processing costs. However, this interplay between linguistic complexity and cognitive processing costs still needs to be investigated by empirical research as up to date there are only a few studies investigating the perception and reception of Easy Language, mostly using offline methods (e.g. questionnaires or retrospective interviews). In contrast to offline methods, which are only capable of assessing comprehension products, online methods allow researchers to track what a participant is focusing their attention on at any given time and to thereby develop a detailed representation of the time-course of cognitive language processing. In our paper, we aim to point out how different online methods (eye-tracking, EEG and fMRI) can be used for investigating the empirical validity of the postulated rules for Easy Language by evaluating cognitive processing efficiency. Besides discussing the applicability of those neuroscientific online methods in Easy Language research, we discuss the importance of collecting personal and neuropsychological data to gain detailed profiles of the participants and therefore not only contribute to the explanation of variance but furthermore to determine the role of neuropsychological skills on reading proficiency. For each online method we elaborate basic principles, discuss some of the main findings in cognitive sciences and demonstrate the greatest advantages but also restrictions of the method and challenges related to the data collection process with impaired participants. Furthermore, we outline current challenges in Easy Language research and summarize remaining research gaps. On a final note, we emphasize that it is both the establishment of online methods and the data triangulation in Easy Language research that enable researchers to gain a profound insight into the cognitive processing of simplified languages.